Marketing Communication in Increasing Room Occupancy at Reddoorsz Hotels During the Covid -19 Pandemic - Ainur Rochmaniah; Adella Eka Ridwanti; Asiyatul Ulfiyah; Rachma Sari Octaviani; Ayu Diah Oktaviana (Kanal: Jurnal Ilmu Komunikasi, 2021)
The Covid -19 pandemic has significantly decreased the occupancy of the RedDoorz Syariah Buduran Sidoarjo Hotel rooms. The objective is to describe the marketing communication strategy used by the RedDoorz Syariah Buduran Hotel in increasing room occupancy. The study used a qualitative research method at the RedDoorz Buduran Hotel in March-August 2020. The information in this study was the hotel manager which was equipped with 3 people and 5 hotel visitors, with a purposive sampling technique which the criteria of hotel managers dan service staff. Observation data observation techniques, open interviews, and documentation. The results show that the RedDoorz Syariah Buduran hotel has carried out digital advertising through social media such as media (Instagram, website and Twitter) and TV advertising (youtube), sales promotion through the distribution of discount vouchers to visitors and holding local scale events, as well as conducting communication through the public relations division by inviting the surrounding community at the hotel anniversary event. The marketing communication strategies that are carried out are integrated with each other, so as to increase the number of visitors during a pandemic.